Sufism in Orientalist studies (Journal of the College of Basic Education, 2023)
First: the concept of SufismIn order to reach the knowledge of the origin and origin of Sufism, I was exposed to the meaning of the word (Sufi + Sufi + Sufism).There are many definitions of the definition of Sufism, and we present some of them:Dream bin Muhammad Al-Baghdadi said ((() Sufism is based on three qualities: adherence to poverty, poverty, and verificationBy giving and abandoning the purpose and choosing)) ©.Al-Junayda was asked about Sufism. He said: Purifying the heart from the approval of the wild and the paradox of natural morals.the suppression of human qualities; And free psychological reasons and fighting spiritual qualities and attachment to sciencereal. And a first use over eternity, advice to all the nation, loyalty to God on the truth, and following the Messenger(PBUH) in Sharia.So all the meanings are all from abandoning the world, self-absorption from it, leaving the homelands, the need for travel, and the prohibition of travelFortunes souls and the elite secrets and breasts. And Sufi on the weight of Awfi, that is, God bless himFaoufi©).The Sufi is one, and the group is Sufi. Whoever achieves this is a Sufi, and the group is Sufi. As for the derivationThe word “tasawwuf”: Al-Qushayri says: “There is no evidence for this name derivation from the Arabic side, nor analogy, and it seems thatA title and whoever says that it is derived from al-Safa or an adjective, then it is far from the point of view of linguistic analogy))©).The derivation is likely to be more than one opinion: there are those who attributed the word to (Sufi), which is the name of a man who had been aloneBy serving God Almighty at His Sacred House, and his name is Al-Ghawth bin Murr. The Sufis were affiliated with him because they resembled himin detachment from God).